Training on Optimizing Waste Bank Management through a Social-Humanistic Approach - Widyastuti, Tri; Wardhana, Ananto Krisna; Paksi, Yudha Febri Al; Ananta Vidada, Irwin; Mawadah, Afrida Nita; Aisyah, Aisyah (Santoso Academy Network, 2024)
Effective waste management in Sumur Mangga RT 06 RW 01, Larangan Ciledug, Tangerang City, remains a significant challenge. The Waste Bank initiative, aimed at organizing waste disposal, faces obstacles including low community engagement and inadequate understanding of waste types and the Waste Bank itself. Additionally, suboptimal prices for collected waste further hinder progress. To address these issues, Bina Sarana Informatika University has launched a Community Service program. This program employs a social humanistic approach to train residents in optimizing Waste Bank management and increasing their income. The methodology involves observation, interviews, training sessions, and evaluations. The outcomes demonstrate enhanced public knowledge and appreciation of waste management and the Waste Bank's role, leading to increased community participation. Training sessions have also equipped residents with strategies to boost the after-sales price of waste, thereby improving their earnings. This initiative has had a positive impact by tackling waste management challenges and enhancing local community welfare. It also emphasizes the importance of enhancing managerial and operational skills among Waste Bank managers, fostering better waste management practices and economic outcomes for residents.